2015
DOI: 10.1080/01932691.2014.956363
|View full text |Cite
|
Sign up to set email alerts
|

Application of Tea Polyphenols to Edible Oil as Antioxidant by W/O Microemulsion

Abstract: The lipophilic properties of tea polyphenols have restricted their application as a natural antioxidant in oils. In order to increase the weight percentage of tea polyphenols in edible oil, a water-in-oil (W/O) microemulsion (ME) of Tween 80/Span 80/ethanol/soybean oil/H 2 O for envelopment of tea polyphenols was prepared. The ternary phase diagram, electrical conductivity, particle size, viscosity, rheological behavior, and oxidation resistance potential of the ME were investigated. The results showed that (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…As reported, the use of composite surfactants will increase the solubilizing capacity, showing a synergistic effect (Porter and others ). In our previous study (Sun and others ), we find the biocompatibility of used surfactant span 80 are not so good, thus in this study, we chose GMO instead of span 80. The HLB of GMO is 3.4, which is similar to that of span (HLB = 4.3), and according to the FDA 21 CFR part, GMO is used in food with no limitation (Krog and others ; Hasenhuettl, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported, the use of composite surfactants will increase the solubilizing capacity, showing a synergistic effect (Porter and others ). In our previous study (Sun and others ), we find the biocompatibility of used surfactant span 80 are not so good, thus in this study, we chose GMO instead of span 80. The HLB of GMO is 3.4, which is similar to that of span (HLB = 4.3), and according to the FDA 21 CFR part, GMO is used in food with no limitation (Krog and others ; Hasenhuettl, ).…”
Section: Resultsmentioning
confidence: 99%
“…The aim of preparation TPs‐loaded MEs is to retard the oxidation of the edible oil, to better understand the encapsulation behavior of ME with TPs, oxidative stability experiment was taken. The anti‐oxidation effect could be assessed by classic chemical analysis of rancidity, POV (Niki and others ; Sun and others ). The POV, expressed as milli‐equivalents (meq) of active oxygen per kg oil, has frequently been used as a simple and rapid method for testing lipid oxidation (Ahn and others ).…”
Section: Resultsmentioning
confidence: 99%
“…Few studies have reported food-grade microemulsions which use long-chain triglycerides or essential oils as the oil phase [14,19]. In our previous studies, food-grade microemulsions based on edible oil and nonionic surfactants were prepared, the phase behavior and the effects of the components in the microemulsions were also examined, which contributed to better understanding the character and the application of food-grade microemulsion in food field [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In food science, microemulsions are used as food supplements to improve the solubility and increase the bioavailability of hydrophobic vitamins, flavors, and other nutrients in water [8][9][10]. Similarly, the hydrophilic bioactive ingredients can also be incorporated into edible oil to protect the oil from undesired degradation [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, it was reported that some antioxidative compounds did not follow the polar paradox due to the partitioning of antioxidants between the oil and water phases. It was reported that antioxidant activity is dependent on different parameters and that polarity is not the only factor to be taken into account [15,16].…”
Section: Introductionmentioning
confidence: 99%